Go Global with Digital Technology-Based Financial Reporting - HAPSARI, Dini Wahjoe; MURTI, Galuh Tresna; SOMA, Mukti; DAMAYANTI, Nensi; FIRMANSYAH, Irvan Wahyu; ROSA, Abigail Ratna; BALDA, Safira (Akuntansi dan Humaniora: Jurnal Pengabdian Masyarakat, 2025)
Sugihmukti Tourism Village is a destination offering natural beauty, educational activities, and local wisdom as its main attractions for tourists. However, despite this enormous potential, administrative management and business process recording remain poorly organized and documented. In response to this situation, efforts were made to increase the capacity of tourism village managers to implement a more efficient digital financial recording and reporting system. Through training and mentoring activities, the team helped managers understand the preparation of financial reports based on MSME standards and introduced the SIABDES Maxi application, which has been tailored to the characteristics and needs of the village. The results of a questionnaire evaluation showed that participants stated that the materials provided were appropriate to their needs, the training delivery was interesting and easy to understand, and the implementation time was deemed effective. Furthermore, the managers hope that similar activities can continue as the need for digitalization of tourism village management increases. This program is expected to strengthen accountability, improve financial governance efficiency, and become a strategic step towards more professional and globally competitive tourism village management.